The effects of molecular and nanoscopic additives on phospholipid membranes - Kumarage, Teshani; Morris, Nicholas B.; Ashkar, Rana (Frontiers in Physics, 2023)
Lipid bilayers -the main matrix of cell membranes -are a paradigm of soft molecular assemblies whose properties have been evolutionarily optimized to satisfy the functional requirements of cells. For instance, lipid bilayers must be rigid enough to serve as the protective barrier between cells and their environment, yet fluid enough to enable the diffusion of proteins and molecular clusters necessary for biological functions. Inspired by their biological multifunctionality, lipid membranes have also been used as a central design element in many practical applications including artificial cells, drug nanocarriers, and biosensors. Whether biological or synthetic, lipid membranes often involve molecular or nanoscopic additives that modulate the membrane properties through various mechanisms. Hence, how lipid membranes respond to additives has justifiably drawn much attention in recent years. This review summarizes findings and observations on different classes of additives and their effects on structural, thermodynamic, elastic, and dynamical membrane properties that are central to biological function or synthetic membrane performance. The review primarily focuses on phospholipids as a major component of cell membranes and a widely used lipid type in synthetic membrane designs.